Les traces du traducteur dans le discours de presse - Lajus, Dorota (Studia Romanica Posnaniensia, 2019)
The interlocutory dialogicality of press discourse manifests itself, among other things, in the use of common expressions that give the impression that “it is the language that speaks, not its users” (Bonhomme, 2012, p. 77). Euphemisms, for example, are used to raise difficult or polemic inducing issues, such as poverty, exclusion, war, politics, etc. Meanwhile, expressions that have become common in the source language, and are consistent with generally accepted norms, do not always remain transparent during the translation process. Depending on the translator’s choices, the phrases used in the target text can have various effects, ranging from the erasure of sensitive topics, to their hyperbolization. The subject of the paper is the comparison of articles published in the French monthly Le Monde diplomatique and their translations, which appeared on the pages of the Polish edition of this periodical. Its aim is to reveal the traces of the translator’s presence, visible through his or her ways of interpreting euphemistic phrases, or toning down harsh expressions.